PENERAPAN SANKSI PIDANA TERHADAP PELAKU PELANGGARAN PRIVASI PADA FITUR TEMAN DEKAT DI INSTAGRAM BERDASARKAN UNDANG- UNDANG NOMOR 19 TAHUN 2016 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI KOTA PEKANBARU - Melati Sukma Dewi; Erdianto Erdianto; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One of the special features on instagram is the close friends feature. The close friendsfeature available on Instagram is useful for making a list or list of close friends from accountowners. The purpose of using the close friends feature on instagram is so that the stories weupload in the form of photos and videos that can only be seen by close friends. It turns out thatthis instagram feature has a drawback, namely it can be a place where someone's privacy isviolated. The usual violation of privacy in this close friends The feature is recording screens orscreenshots of posts and distributing them to the public without permission. Dissemination ofprivate electronic information to the public is a form of privacy violation. If theupload capture/screenshot contains personal data including name, writing, and/or images thatcan identify a person then the distribution via electronic media must be carried out with theconsent of the person confirmed, according to Article 26 paragraph (1) Law 19/2016 . For thisact, every person whose rights have been violated, in this case the victim, can submit a lawsuitfor the harm incurred.The purpose of this study is to find out the application of criminal sanctions toperpetrators of privacy violations in the close friends feature on Instagram, in accordance withLaw Number 19 of 2016, Amendments to Law Number 11 of 2008 concerning information andelectronic transactions in Pekanbaru City. Second, to know obstacles in the implementation ofcriminal sanctions against perpetrators of privacy violations in the "close friends" feature onInstagram based on law number 19 of 2016, an amendment to law number 11 of 2008concerning information and electronic transactions in the city of Pekanbaru.This researchmethod can be classified into the type of sociological legal research as research that wants tosee the unity between law and society with the gap between das sollen and das sein.The conclusion from the results of the study that to provide a deterrent effect on theapplication of criminal sanctions against perpetrators of privacy violations on the close friendsfeature on Instagram is imprisonment. However, the application of these criminal sanctions isonly related to cases containing pornographic elements. Meanwhile, violations of privacy onsocial media, such as those related to defamation, can be resolved non-penal (outside court) orresolved through retorative justice. Efforts that can be made to deal with obstacles in theapplication of criminal sanctions are that law enforcers work together with expert sanctions,both linguist sanctions, to identify forms of privacy violations that can be categorized aswhether it is a privacy violation or not.Keywords: Privacy Violation – Social Media – Instagram - ITE